Analisis tentang Pelaksanaan Sistem Jaminan Sosial Kesehatan Pasca Putusan Mahkamah Konstitusi No. 07/PUU-III/2005 - Muh. Kadarisman (Fakultas Hukum Universitas Islam Indonesia, 2015)
This study aims at analyzing the implementation of Law No. 40 of 2004 related to the Health Social Security after the Constitutional Court decision No. 07 / PUU-III / 2005. The reseacher uses library research method with content analysis approach. The research result highlights that: the implementation of Law No. 40 of 2004 related to the Health Social Security after the Constitutional Court decision No. 07 / PUU-III / 2005, whose implementation is entrusted to BPJS is still far from fairness for all. The application of Health Social Security BPJS is still problematic in many ways, among which since it implements a tiered service flow prior to the hospital, that is the participants must first check into the first-level health facilities (health centers) before being referred to the hospital. Another problem is regarding the complexity of the service flow of BPJS for implementing a tiered service flow.